Psychological empowerment as a mediating and multidimensional construct : an empirical examination of key antecedents and consequences within a public health service organisation: a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Psychology at Massey University - Johnston, Peter (Massey University, 2000)
This study continues the work initiated by Spreitzer (1995a) in operationalising and measuring psychological empowerment and examining the construct in relation to key antecedents and consequences. Psychological empowerment was defined as a gestalt of four dimensions reflecting an active orientation to one's work role. These dimensions are meaning, competence, self-determination and impact. Tested hypotheses concerned the relationship between empowerment and interpersonal trust, supervisor support, peer cohesion, access to resources, access to strategic information, conscientiousness (antecedents), job satisfaction, and affective organisational commitment (consequences). The structural validity of the empowerment scale was investigated, as was the mediating role of psychological empowerment in the proposed model. Partial support was found for the hypotheses relating empowerment to interpersonal trust, supervisor support, access to strategic information, job satisfaction, and affective organisational commitment, and strong support was found for the hypothesis relating empowerment to conscientiousness. No support was found for the hypotheses relating empowerment to peer cohesion and access to resources, and limited support was found for the mediating role of empowerment. A principle components factor analysis supported the four-factor model of psychological empowerment. The results highlight the advantages of adopting a multidimensional approach in the study of psychological empowerment. Implications for organisations, study limitations, and directions for future research are discussed.
Keywords: Employee empowerment; Public health personnel -- Management